Pengaruh Efisiensi Modal Kerja Terhadap Rentabilitas Ekonomi Pada Koperasi Telatang Mandiri Kecamatan Merapi Barat Kabupaten Lahat - Darwin Kesuma (Sekolah Tinggi Ilmu Ekonomi (STIE) Serelo Lahat, 2020)
Telatang Mandiri Cooperative West Merapi Lahat Regency is one of the new cooperatives. In maintaining its business for the welfare of its members, Telatang Mandiri Cooperative West Merapi Lahat Regency has economic rentability problem, where the ratio of economic profitability from 2011 to 2015 always decreases. One of the cause is the inefficient of working capital management. Therefore, the research was conducted with the aim to find out how the effect of working capital efficiency on the achievement of economic profitability in the Cooperative Telatang Mandiri West Merapi Lahat regency. The research method used in this research is simple linear regression analysis. Sources of data used in this study are the financial statements recorded by the Telatang Mandiri Cooperative West Merapi Lahat Regency period 2011-2015. Based on the research results obtained regression equation Y = 0,008 + 0,919X + e. The correlation coefficient obtained r = 0.977 which has a very strong relationship, this is supported by the analysis of coefficient of determination of 95.4% and the rest of 4.6% influenced by other factors. Also supported by t test obtained t calculate 7,861> t table 2,353 which mean working capital efficiency have an effect on signifikan to economic profitability. Based on the research, it can be concluded that there is a positive and significant effect of working capital efficiency on economic profitability in Telatang Mandiri Cooperative West Merapi Lahat Regency.